2013
DOI: 10.1136/neurintsurg-2013-010870.9
|View full text |Cite
|
Sign up to set email alerts
|

O-009 Safety of flow diversion: Results from a multicentre registry

Abstract: Purpose To determine the rates of neurologic adverse events following Pipeline Embolic Device (PED) placement for intracranial aneurysm treatment. Methods A retrospective review of medical records was performed at 19 centres to identify consecutive intracranial aneurysms treated with the PED following regulatory approval for marketing the device in the given country. All patients in whom at least one PED was placed and in whom follow-up was available prior to IRB or ethics panel approval were enrolled. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Two of these cases were treated with parent artery occlusion while the other was managed with transvenous coil embolization. The incidence of delayed spontaneous aneurysm rupture after treatment with a flow diverter ranges from 0.6% to 1% 7 8 12. The only identifiable risk factor for delayed rupture is size of 10 mm or greater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these cases were treated with parent artery occlusion while the other was managed with transvenous coil embolization. The incidence of delayed spontaneous aneurysm rupture after treatment with a flow diverter ranges from 0.6% to 1% 7 8 12. The only identifiable risk factor for delayed rupture is size of 10 mm or greater.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the International Retrospective Study of Pipeline Embolization Device (IntrePED) registry of 580 aneurysms treated worldwide with PED revealed only three spontaneous aneurysm ruptures after PED implantation, an incidence of 0.6% 7. Additionally, the European Society of Minimally Invasive Neurological Therapies (ESMINT) Retrospective Analysis of Delayed Aneurysm Ruptures (RADAR) study found 14 delayed aneurysm ruptures among 1421 aneurysms treated with flow diverters, an incidence of 1% 8…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that intraaneurysmal coil embolization is not an effective treatment option for large or giant CCA. [6] According to a recent report, a flow diverting stent has been developed for the effective treatment of an unruptured giant symptomatic CCA; [7] however, early, [8] and delayed [9,10] rupture of the aneurysm after treatment has been described. The incidence delayed ruptured of an aneurysm after the stent is 0.6-1%, but was not reported for early rupture.…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent report, a flow diverting stent has been developed for the effective treatment of an unruptured giant symptomatic CCA;[ 38 ] however, early,[ 39 ] and delayed[ 40 41 ] rupture of the aneurysm after treatment has been described. The incidence delayed ruptured of an aneurysm after the stent is 0.6–1%, but was not reported for early rupture.…”
Section: Endovascular Treatmentmentioning
confidence: 99%